(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This work presents a photographic album about an original folk expression of Huajuapan de Leon Heroic City, Oaxaca; where there are sculptures who dancing to wind bands sounds through the streets of the town and are known as the matachines of the Saint Joseph neighborhood. These sculptures personify real and mystical characters such as devils, clowns, celebrities or politicians. The matachines are made up of a carved head of colorin or pipi wood, which is covered with plaster and decorated with oil paint according to each character. They have a frame called huacal, which is made of pine wood and is used by a dancer to carry the matachin on his shoulders. Their clothing is made according to each character and they have arms made with blanket fabric and sawdust. Every year in March, the matachines make glad the festival of the chirundos neighborhood; they recall the ancient celebrations of victories by Christians over the Moors and dances symbolizing the struggle between good and evil.